Kebijakan Indonesia Tidak Meratifikasi Konvensi ILO No. 188/2007 tentang Pekerjaan Penangkapan Ikan - Ahda Mujahidah Ibrahim (Indonesian Perspective, 2023)
This research aims to explain why Indonesia did not ratify the ILO Convention No. 188/2007. The technique of data collection was conducted with literature study using primary sources in the form of ILO Convention No. 188/2007, and Recommendation, 2007, Law No. 15 of 2016 regarding the Ratification of Maritime Labour Convention, 2006 and secondary sources from data, documents, or reports related with the topic of this thesis. The results of this study showed that the reason why Indonesia did not ratify the ILO Convention No. 188/2007 is based on Indonesia’s rational choices that related to the consideration of profit and loss calculations in order to maximize the profits and minimize the costs in the decision-making process. Indonesia’s profits are not comparable to the economics costs and the administrative burden in reporting and implementing the ILO Convention No. 188/2007. In addition, the ratification of the convention is still not an urgency for the Ministry of Manpower because the Ministry of Manpower considers that the regulations are sufficient in providing protection for fishermen. This is also supported by the fact that only 19 ILO member countries have ratified ILO Convention No. 188 of 2007 so that it does not have a significant impact on Indonesian fishermen.